The Effectiveness of QRIS Usage as a Digital Transaction Tool for Youth in Blora Regency - Sriantika, Elsa; Abidin, Ali Zainal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This study examines the effectiveness of QRIS usage among the youth in the Blora Regency. This research aims to determine the effectiveness of QRIS as a digital transaction tool and to observe the behavioral patterns of QRIS usage within the youth community in the Blora Regency. Blora Regency was randomly selected as the research area, focusing on a region that has not been widely publicized. The research approach is qualitative, with data from primary sources through questionnaires. A total sampling of 104 respondents, aged 15-35 years residing in Blora Regency, was used. To ensure sufficient information and data saturation, we selected 104 respondents, focusing on respondent variation to identify key elements influencing the phenomenon under study. Data collection in this study employed closed questionnaires, and the data analysis method was qualitative descriptive with content analysis, along with source triangulation for data validity. The use of this method, with random selection of informants from the youth of Blora Regency, allows for diverse perspectives on QRIS, reducing bias in the analysis. The study results indicate that QRIS in Blora Regency is less effective because not all places accept QRIS. To enhance QRIS effectiveness, we need to actively expand the network of places that accept QRIS and increase awareness among the younger generation. Regarding youth behavior towards QRIS, their primary motivation for using QRIS is a personal experience, but the recommendation level of QRIS to others tends to be low. These findings highlight the need to address security issues and improve infrastructure for better QRIS effectiveness.